Segregation in stored grain bulks: Kinematics, dynamics, mechanisms, and minimization – A review. (March 2019) - Jian, Fuji; Narendran, Ramasamy B.; Jayas, Digvir S.
Abstract: Stored grain is a mixture of grain kernels, dockage, and foreign materials. During the handling of grain bulks, segregation is a natural tendency of the grain mixture components differing in some properties such as size, shape, density, particle surface roughness, electrostatic charge, chemical affinities and stability, and/or thermal stability. Segregation causes many grain storage problems such as uneven distribution of airflow rate during grain drying and aeration. Due to the importance of uniform distribution of dockage and foreign material inside stored grain bins, minimization of segregation during grain storage and handling is necessary. This review characterized the kinematics and dynamics of segregation during grain loading and unloading, classified segregation mechanisms of grain bulks to four categories (trajectory, fluidization, shifting, and impact), identified the factors influencing the segregation, analyzed the relationship between airflow resistance and segregation, summarized the studies on the mathematical modeling of segregation, and provided the suggestions on the minimization of segregation. Mixtures consisting of multiple components and broad particle size distributions pose even greater difficulties in predicting segregation. Among these difficulties, the impediment is that there are few studies available to identify the segregation during grain handling. Therefore, conducting further studies on the segregation of grain mixtures in the future would be helpful.